Penerapan Konseling Analisis Transaksional dalam Peningkatan self-confidence untuk berprestasi akademik Pada Peserta Didik SMP Negeri 8 Malalayang Manado Sulawesi Utara - Ariantje J.A. Sundah (Peneliti.net, 2021)
Self-confidence as a self-recognition becomes a life position. This research was carried out with the aim of increasing the self-confidence of the members of the group consisting of 10 students of class VII SMP Negeri 8 Malalayang Manado, North Sulawesi through group counseling analysis transacsional. This research was carried out quantitatively through a quasi-experimental method. The subject's self-confidence was measured by the same questionnaire before and after being given treatment, so that different analysis results could be obtained. The results of data analysis showed that the value of t count was 6369. the value of t table is 1.633. Thus the results of the analysis obtained the value of t arithmetic 9.352 > 1.633 which means there is a significant difference between the pretest and posttest; it shows that there is a significant effect on the use of transactional analysis counseling in increasing the confidence of research subjects. It is concluded that the implementation of group transactional analysis counseling can increase self-confidence. As a recommendation, it can be found that school counselors need to gain an understanding of the implementation of transactional analysis counseling, especially to help students who tend to have problems in learning.